Kajian Morfometri Spermatozoa Sugar Glider (Petaurus Breviceps Papuanus) - Fifit Natalia (2015)
This study aims to analyze spermatozoa morphometry of sugar glider (Petaurus breviceps papuanus). Semen samples were collected from three mature male sugar gliders using manual manipulation technique and cauda epididymal mincing technique. Semen samples were stained using eosin negrosin. Spermatozoa morphometry were measured for head length, width, area and perimeter, mid piece tail, primary tail, and total spermatozoa length using lmage Raster Software. The results indicates two variations of spermatozoa shape that are spear-shaped and Tshaped. Morphometry of spear-shaped spermatozoa from cauda epididymal mincing technique were 5.97 ± 0.44 μm HL and 3.03 ± 0.36 μm HW; 16.96 ± 2.26 μm2 A and 16.00 ± 1.01 μm P; 6.70 ± 0.57 μm MPTL•and 78.50 ± 3.21 μm PTL; and 91.13 ± 3.28 μm TSL. Analysis of T-shaped spermatozoa obtained from cauda epididymal mincing technique show 3.49 ± 0.8 μm HL and 6.22 ± 0.52 μm HW; 17.98 ± 4.22 μm2 A and 16.6 ± 1.64 μm P; 7.4 ± 0.66 μm MPTL and 78.31 I ± 2.76 μm PTL; and 89.2 ± 2.89 μm TSL. Another result of spermatozoa morphometry from spear-shaped obtained from manual manipulated technique shown 6.36 ± 0.429 μm HL and 3.40 ± 0.53 μm HW; 16.35 ± 1.35 μm2 A and 15.50 ± 0.74 μm P; 6.71 ± 0.40 μm MPTL and 57.20 ± 8.04 μm PTL; and 70.27 ± 8.26 μm TSL.